Bahasa Visual Film Pendek Vertikal dalam Membangun Narasi Intim pada Media Sosial - Pijar Bintang Tutuko; Aryo Bayu Wibisono; Alfian Candra A (Jurnal Kajian dan Penelitian Umum, 2026)
The development of social media and smartphone usage has driven changes in the production and consumption of audiovisual content, particularly through vertical video formats. This study aims to analyze how visual language in vertical short films is used to construct intimate narratives. The focus of this research includes cinematographic elements such as framing, composition, shot size, and spatial arrangement within the 9:16 format. A qualitative approach is employed through visual observation and documentation of vertical short films by Roman Adolfo and Mesh Virwani published on social media. The data are analyzed descriptively to identify the role of visual elements in narrative delivery. The results indicate that vertical orientation influences visual strategies, with centered compositions and the dominance of medium shots to close-ups. Limited lateral space encourages vertical spatial use and the application of color and framing to enhance emotional expression. Vertical short films provide a more personal and intimate viewing experience and represent an adaptation of cinematic visual language within the digital media ecosystem.